Attosecond time delays in the photoionization of noble gas atoms studied in TDLDA - Maia Magrakvelidze (14410392) (2015)
Synopsis We perform time-dependent local density functional calculations of the quantum phase and time delays of valence photoionization of noble gas atoms. Results may be accessed by XUV-IR interferometric metrology. Other Information Published in: Journal of Physics: Conference Series License: http://creativecommons.org/licenses/by/3.0/ See article on publisher's website: https://dx.doi.org/10.1088/1742-6596/635/9/092038